A produção de edifícios diante dos novos paradigmas informacionais e da tecnologia BIM com a contribuição da gestão e organização do conhecimento - Mário Lucio Pereira Junior (2019)
The activities of Architecture and Engineering are characterized by their essentially propositional nature. These professionals spend much of their time in activities that contain decision making and aim at transforming a reality through a plan and construction: the production of buildings. Decision making is a next step to creating meaning and building knowledge. For every decision making, knowledge generation is necessary. Thus, in the production of buildings, work with knowledge is an inherent characteristic. More recently, this activity started to have a new paradigm that involves three points: the introduction of new technology Internet of Things; the change in the configuration of the work for a collaborative and simultaneous arrangement; and the introduction of new building tools, representation and documentation or Building Information Modeling. As object of the present work are the new paradigms of the Architecture and the production of buildings, the dissemination of the Knowledge Organization & Management in the diverse areas of human activity and the new challenges of the formal education in Architecture and Engineering. The research problem was: How to improve the production of buildings in the face of new informational paradigms, which involve Building Information Modeling (BIM), collaborative and simultaneous project, internet of things, smart buildings and smart cities, with the contribution of Knowledge Organization & Management? The general goal was to propose guidelines for production of buildings, considering its new paradigm as an informational phenomenon, in the context of Architecture, Engineering and Construction. The specific objectives were: to describe and characterize new architecture paradigms and the production of buildings and the specificities of spatial representation; to gather and discuss the theoretical and methodological foundations on the Knowledge Organization & Management, especially the collaboration and the ontologies, applicable to the domain; compare and develop the relationships between the needs presented by the paradigms of the production of buildings and the Knowledge Organization & Management. The justification for this research is the need to gather studies on theories and methodologies of Knowledge Organization & Management that contribute to its development and meet the recent needs of the production of buildings. As for nature, the research was classified as applied research, regarding the approach of the problem as a qualitative research, regarding the objectives as exploratory research. The present work is a panoramic study on aspects of Information Science and Architecture and Engineering. The theoretical references were Information and Knowledge Management, Collaboration, Knowledge Organization Systems, Ontology, Computer Aided Design, Building Information Modeling, Simultaneous Design, Sustainability, Internet of Things, Smart Building, Smart Cities, Smart Life. As a result, the relations between the questions presented by the paradigms of the production of buildings and the Knowledge Organization & Management were elaborated and discussed, and behavioral and procedural guidelines were presented for production of buildings, considering its new paradigm, as an informational phenomenon. This work is expected to contribute to the improvement of the production of buildings and the strengthening of relations between the areas, in favor of mutual benefits, always motivated by sustainability and preservation of the planet and life.